Pelatihan Membuat Media e-Biblioterapi pada Guru Sekolah Dasar Kota Kediri - Ratnawati, Vivi; Nurfahrudianto, Aan; Ningsih, Risaniati; Aurora, Flora Fahimna; Ugiutami, Adita Nani (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2025)
The low interest in reading in Indonesia has led to a lag in information and literacy culture which is very important for developed countries. Initial observations show that 75% of students at SDN Ngadirejo 5 get low scores in literacy and numeracy. AKM also shows that the level of numeracy literacy is still lacking and needs to be improved. Group guidance services using e-bibliotherapy techniques aim to develop students' socialization and communication skills. The efforts made are by providing training in creating e-bibliotherapy media with the stages of needs analysis, socialization, training, implementation and mentoring as well as evaluation. The application used is Canva and media to publish web-based teacher work. From the community service activities that have been carried out, it can be concluded that training in making e-bibliotherapy media for teachers in elementary schools in the city of Kediri is very useful. The visible benefit is that teachers are able to create e-bibliotherapy media as an effort to improve literacy and numeracy competencies. Apart from that, teachers are starting to want to apply the skills they already have to create multimedia that can be directly applied in the learning process.